Foil stiffness optimization of a gas lubricated thrust foil bearing in enhancing load carrying capability. (2022) - Supreeth, S.; Ravikumar, R.N.; Raju, T.N.; Dharshan, K.
Abstract: Air Foil Thrust Bearings (AFTB) are self-acting hydrodynamic members that support axial loads of high-speed rotating turbo-machineries. The load bearing capacity of such bearings mainly depends on the foil structure. The proposed Foil Thrust Bearing of 60 mm in diameter, designed and fabricated for performance evaluation, consists of a single top foil with an inner edge height equal to that of outer edge. This paper focuses on optimizing the foil stiffness in terms of foil thickness for steel and copper foil material with 60° and 90° sector angles. Various configurations of Gas Foil Thrust Bearings (GFTB) are tested for structural stiffness and thrust loads at higher operating speeds with an instrumented test rig dedicated for the purpose. Both geometric and operating parameters are varied to determine the best possible foil stiffness that enhances the load carrying capability of the Air Foil Thrust Bearing operating under hydrodynamic condition. CFD Simulation is also carried out to indicate the pressure distribution on the foil surface for the said bearing at actual boundary conditions.